Analysis of Poverty Rate and Stunting Prevalence in The Province of Aceh - Arfah Husna; Dadang Sukandar (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
The purpose of this research is to classify districts in Aceh Province based on indicators of poverty and stunting prevalence rates. The data used is cross-section data for 2022, including the poverty severity index, poverty depth index, the percentage of poor people, and the prevalence of stunting from the 2022 SSGI results. The method used is cluster analysis, utilizing poverty percentage data (P0) to determine clusters and analyze the difference between district clusters and the average stunting rate. Based on the analysis results, it can be concluded that poverty at the district level is grouped into three categories. Group 1 consists of districts such as Aceh Besar, Aceh Jaya, Aceh Tamiang, Central Aceh, Southeast Aceh, Biruen, Banda Aceh, Langsa, Sabang, and East Aceh. Group 2 includes the Regencies of West Aceh, Southwest Aceh, North Aceh, Nagan Raya, Lhokseumawe, and Subussalaam. Group 3 comprises Singkil, Bener Meriah, Gayo Lues, Pidie, Pidie Jaya, and Simeulu Regencies. The cluster analysis reveals that districts with lower poverty rates are in group 1, while group 2 exhibits moderate poverty, and group 3 experiences a high poverty index. Furthermore, the results of the correlation analysis show that there is a positive correlation between the percentage of stunting prevalence and the percentage of poverty with a real relationship and the correlation is significant.